CRL4Mahj E3 ubiquitin ligase promotes neural stem cell reactivation. - Ly, P.T.; Tan, Y.S.; Koe, C.T.; Zhang, Y.; Xie, G.; Endow, S.; Deng, W.M.; Yu, F.; Wang, H. (PLoS Biology, 2019)
The ability of neural stem cells (NSCs) to transit between quiescence and proliferation is crucial for brain development and homeostasis. Drosophila Hippo pathway maintains NSC quiescence, but its regulation during brain development remains unknown. Here, we show that CRL4Mahj, an evolutionarily conserved E3 ubiquitin ligase, is essential for NSC reactivation (exit from quiescence). We demonstrate that damaged DNA-binding protein 1 (DDB1) and Cullin4, two core components of Cullin4-RING ligase (CRL4), are intrinsically required for NSC reactivation. We have identified a substrate receptor of CRL4, Mahjong (Mahj), which is necessary and sufficient for NSC reactivation. Moreover, we show that CRL4Mahj forms a protein complex with Warts (Wts/large tumor suppressor [Lats]), a kinase of the Hippo signaling pathway, and Mahj promotes the ubiquitination of Wts. Our genetic analyses further support the conclusion that CRL4Mahj triggers NSC reactivation by inhibition of Wts. Given that Cullin4B mutations cause mental retardation and cerebral malformation, similar regulatory mechanisms may be applied to the human brain.